2018
DOI: 10.1021/acs.jpcb.8b09343
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Molecular Dynamics Study of Effects of Small-Molecule Organic Acids on PMIA Thermal Decomposition

Abstract: Reactive molecular dynamics was used to investigate the atomic-level mechanism of formic acid-accelerated deterioration of meta-aramid (PMIA) fibers. The simulation results showed that formic acid promoted PMIA decomposition. The activation energy of a composite system (PF) consisting of formic acid and PMIA was 106.94 kJ/mol at 2000–3000 K, which is 11.95% lower than that of pure PMIA. The main small-molecule products of the PF system were H/C/O-containing molecules (H2O, CO, and CO2), hydrocarbon molecules (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In recent years, numerous studies have focused on the thermal aging mechanism of insulation paper. Although the aging process and its mechanism on oil–paper in transformers have been investigated [8,9,10,11,12,13,14,15,16,17,18], the thermal stability of meta-aramid insulation paper in transformers at operating temperature has not been analyzed. Therefore, it remains important to examine the thermal stability and thermal aging mechanism of crystalline and amorphous regions in meta-aramid insulation paper.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous studies have focused on the thermal aging mechanism of insulation paper. Although the aging process and its mechanism on oil–paper in transformers have been investigated [8,9,10,11,12,13,14,15,16,17,18], the thermal stability of meta-aramid insulation paper in transformers at operating temperature has not been analyzed. Therefore, it remains important to examine the thermal stability and thermal aging mechanism of crystalline and amorphous regions in meta-aramid insulation paper.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocyanic acid, which was produced at high temperatures, could be used to detect thermal faults in PMIA. In another work they published that same year [93], the effects of small organic acids were studied, and formic acid was proved to accelerate the thermal aging of PMIA.…”
Section: Thermal Agingmentioning
confidence: 99%
“…Reaction molecular dynamics such as Yin F [30] were used to study the atomic-scale mechanism of formic acid-accelerated meta-aramid (PMIA) fiber degradation. The simulation results showed that formic acid promoted the decomposition of PMIA.…”
Section: Aging Properties Of Aramid Fibersmentioning
confidence: 99%